Prognostic impact of human papillomavirus status, survivin, and epidermal growth factor receptor expression on survival in patients treated with radiochemotherapy for very advanced nonresectable oropharyngeal cancer1. Issue 9 (5th October 2012) - Semrau, Robert; Duerbaum, Helena; Temming, Susanne; Huebbers, Christian; Stenner, Markus; Drebber, Uta; Klussmann, Jens Peter; Müller, Rolf‐Peter; Preuss, Simon F.
Abstract Background The influence of human papillomavirus (HPV) status on survival for patients with very advanced inoperable oropharyngeal SCC treated with radiochemotherapy (RCT) was studied. Methods Patients received either 69.2 Gy with concomitant boost (ccb) or 70 Gy conventionally fractionated (cf), weekly paclitaxel 40 mg/m2, and carboplatin area under the concentration–time curve (AUC) 1. Tumor was analyzed for the presence of high‐risk HPV‐DNA using polymerase chain reaction (PCR) and direct DNA sequencing. p16‐expression, survivin, and epidermal growth factor receptor (EGFR) expression were evaluated by immunohistochemistry and influence on survival was calculated. Results Of 52 patients, 25.0% were HPV positive and 75.0% HPV negative. The 2‐year progression‐free survival (PFS) was 70.1% for p16‐positive patients and 37.1% for p16‐negative patients (p = .005). The 3‐year overall survival (OS) rate was 43.9% for all patients and did not significantly differ between the groups. Neither survivin nor EGFR expression influenced PFS or OS significantly. Conclusions HPV status influences PFS in patients with advanced, nonresectable tumor stages but not OS. Additional risk factors seem to have a stronger influence on survival than HPV status. © 2012 Wiley Periodicals, Inc. Head Neck, 2013